METHOD OF PROOF INVARIABLY IMAGES IN THE COMPUTER!TECHNICAL EXPERTISE "FROM EXPERT PRACTICE# - N. Khatuntsev; A. Lizorkin (Теория и практика судебной экспертизы)
The possibility of research "les of image formats for changes after creation, through Hu#man tables and Quantization tables analysis are discussed.